2014
DOI: 10.1159/000362714
|View full text |Cite
|
Sign up to set email alerts
|

Non-Dipping Heart Rate and Microalbuminuria in Type 2 Diabetes Mellitus

Abstract: Objectives: The aim of this study was to identify factors which are independently associated with non-dipping heart rate (HR) in a type 2 diabetic population at high risk of cardiovascular disease. Methods: The study recruited 179 type 2 diabetic subjects with a mean diabetes duration of 18.3 years and with proliferative retinopathy. All underwent 24-hour blood pressure and HR monitoring, and were assessed for markers of inflammation, insulin resistance, albuminuria, presence of peripheral neuropathy and perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…The authors observed that night-time ambulatory HR was a significant predictor of fatal and non-fatal cardiovascular events [25]. Non dipping status for HR is also a negative predictor in diabetic patients: Magri et al found that non dipping pattern for HR, in these patients, was associated with development of microalbuminuria [26]. In chronic kidney disease elevated night-time HR was found to be associated with an increased arterial stiffness [27].…”
Section: Characteristics Of Cardiovascular Autonomic Dysfunction Detementioning
confidence: 99%
“…The authors observed that night-time ambulatory HR was a significant predictor of fatal and non-fatal cardiovascular events [25]. Non dipping status for HR is also a negative predictor in diabetic patients: Magri et al found that non dipping pattern for HR, in these patients, was associated with development of microalbuminuria [26]. In chronic kidney disease elevated night-time HR was found to be associated with an increased arterial stiffness [27].…”
Section: Characteristics Of Cardiovascular Autonomic Dysfunction Detementioning
confidence: 99%
“…The presence or absence of (normal) nocturnal falls in BP, called dipping, is also implicated in diabetic vascular complication risk. Whilst best studied in diabetic nephropathy [198], non-dipping overnight blood pressure has also been associated with increased risk of diabetic retinopathy in type 2 diabetes subjects [199].…”
Section: Blood Pressurementioning
confidence: 99%
“…The question of whether ANS dysfunction in diabetics is merely a marker or causative factor to target end-organ damage (TOD), including retinopathy, nephropathy and CV complications, has continued to stimulate research interest. To that end, the study relating microalbuminuria, high platelet counts and non-dipping HR in patients with T2DM by Magri et al [5] in this issue of Cardiology is a welcome addition to an already existing pool of studies.…”
mentioning
confidence: 99%
“…The main finding of the study is that patients with non-dipping HR independently had a significantly higher logarithmic albumin-creatinine ratio and higher platelet counts. The authors conclude that non-dipping HR might give an indication of underlying generalized atherosclerosis in diabetic patients [5]. …”
mentioning
confidence: 99%
See 1 more Smart Citation